Supporting Patients With Untreated Prostate Cancer on Active Surveillance: What Causes an Increase in Anxiety During the First 10 Months? - Alvisi, Maria Francesca; Dordoni, Paola; Rancati, Tiziana; Avuzzi, Barbara; Nicolai, Nicola; Badenchini, Fabio; De Luca, Letizia; Magnani, Tiziana; Marenghi, Cristina; Menichetti, Julia; Silvia, Villa; Fabiana, Zollo; et al. (Frontiers in Psychology, 2020)
Background. The psychological burden possibly deriving from not immediately undergoing radical treatment for prostate cancer (PCa) could be a potential disadvantage of Active Surveillance (AS), especially in the eve of some relevant clinical exams (i.e. re-biopsy, PSA test and medical examination). Even if it is known from the literature that the majority of PCa men in AS do not report heightened anxiety, there is a minority of patients who shows clinically significant levels of anxiety after diagnosis. The present study aimed to investigate if demographic, clinical and psychological variables at the entrance in AS (T0) were associated with the risk of developing clinically significant PCa-related anxiety 2 months before the first re-biopsy (T1), and to offer psychological support to improve quality of life (QoL). Materials and Methods. 236 patients participated in the Prostate Cancer Research International: AS (PRIAS) protocol and in PRIAS-QoL study. Demographic/clinical features, health-related QoL domains, coping with cancer, PCa-related anxiety (Memorial Anxiety Scale for PCa, MAX-PC), personality traits and decision-making-related factors were assessed at T0. MAX-PC was also administered at T1. PCa-related anxiety at T1 was considered to be of clinical significance if the MAX-PC score was ≥1.5. Multivariable logistic regression coupled to bootstrap was used to detect factors associated with high levels of anxiety. Results. The median age was 64.4 years. 56 patients (24%) reported MAX-PC total score above the cut-off. Three factors were associated with a high level of PCa-anxiety at T1: anxious preoccupation (OR=4.36), extraversion (OR=1.9) and prostate-related symptoms (median OR=0.46). Physical well-being resulted to be associated with a low PCa-anxiety subscale (median OR=0.15); Neuroticism and Functional well-being were associated with PSA anxiety (median OR=7.05 and 0.73, respectively). Neuroticism and Helplessness/Hopelessness resulted associated with fear of progression (median OR=18.1 and 5.8, respectively). Conclusion. Only Aa minority partial portion of patients the sample experienced significant levels of anxiety after ten months. Psychological assessment should be routinely conducted to detect risk factors (i.e. anxious preoccupation, extraversion) for increased anxiety, offering tailored psychological interventions aimed at promoting interpersonal awareness and emotional well-being.